KEMAMPUAN OPINI AUDIT TAHUN SEBELUMNYA MEMODERASI PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS PADA “OPINI AUDIT GOING CONCERN” - Benny, I Made Priyana; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
Factors such as profitability, leverage and liquidity alleged is not always linear influential in an audit opinion going concern because factors are the contingency, one of them is prior year auditor opinion. This study attempts to test the ability of an audit opinion last year profitability moderating influence , leverage and liquidity on an audit opinion going concern .A method of sample the determination of using a technique of sampling purposive where appropriate criteria determined by obtained 20 companies .The data in this study collected through a method of observation non participants by downloading data from bei to companies manufacturing 2010-2013 the period .The testing of hypotheses to research was used in the logistic regression analysis . This research result indicates that an audit opinion previous year capable of moderating influence leverage on an audit opinion going concern , while an audit opinion the previous year not capable of moderating influence profitability and liquidity on an audit opinion going concern .
Keywords: audit opinion going concern, prior year auditor opinion, profitability, leverage, liquidity